Development of a high-throughput bioassay to determine the rate of antimalarial drug action using fluorescent vitality probes - Laming, Dustin (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
Malaria is one of the most prevalent diseases in Africa and the Plasmodium falciparum species is widely accepted as the most virulent, with a fatality rate of 15 "“ 20 % of reported cases of infection. While various treatments have been accepted into early stage clinical trials there has been little progress towards a proven vaccine. Pending a long term solution, endemic countries rely heavily on the development of innovative drugs with acute efficacy coupled with rapids mode of action. Until recently the rate of drug action has been measured by light microscopic examination of parasite morphology using blood slides of drug treated parasite cultures at regular time intervals. This technique is tedious and, most importantly, subject to interpretation with regards to distinguishing between viable and comprised parasite cells, thus making it impossible to objectively quantitate the rate of drug action. This study aimed to develop a series of bioassays using the calcein-acetoxymethyl and propidium iodide vitality probes which would allow the rate of drug action on Plasmodium falciparum malaria parasites to be assessed and ranked in relation to each other. A novel bioassay using these fluorescent vitality probes coupled with fluorescence microscopy was developed and optimized and allowed the rate of drug action on malaria parasites to be assessed i) rapidly (in relation to current assay techniques) and ii) in a semi-quantitative manner. Extrapolation to flow cytometry for improved quantification provided favourable rankings of drug killing rates in the pilot study, however, requires further development to increase throughput and approach the ultimate goal of producing a medium-throughput assay for rapidly assessing the rate of action of antimalarial drugs. Attempts to adapt the assay for use in a multiwell plate reader, as well as using ATP measurements as an indication of parasite vitality after drug treatment, was met with erratic results. The viability probes assay as it stands represents an improvement on other assay formats in terms of rapidity and quantification of live/compromised parasites in cultures.
Keywords: Malaria -- Africa; Plasmodium falciparum; Drug development; Fluorescence